Subsets of cerebrospinal fluid lymphocytes in acute pediatric respiratory viral infection with meningeal syndrome - A. A. Zhirkov (SPb RAACI, 2020)
Current urgency of studying the intrathecal cellular immune response to infections of central nervous system is determined by limited knowledge on existing data about mechanisms of the brain immune protection in normal and diseased state. Implication of multi-colour flow cytometry in clinical laboratory diagnostics allowed to perform detailed studies of biological liquors, including cerebrospinal fluid (CSF). Currently, however, there are only scarce data on the lymphocyte subpopulations in CSF. Appropriate reference values remain a challenging issue. A study of CSF lymphocyte pool in absence of definite results at previous examination may be a potential way to resolve this problem. These clinical conditions include acute respiratory viral infections (ARVI), presenting with pseudomeningitidis (meningism) syndrome. The aim of this work was to characterize the subsets of lymphocytes from CSF of the children with ARVI with the meningism symptoms in order to get basic (control) values for diagnostics of inflammatory brain diseases. We have studied subpopulation composition of the CSF lymphocytes form in 27 children with ARVI complicated by the meningism (pseudomeningitidis) by means of flow cytometry using FACSCalibur analyzer with BD MultiTEST IMK Kit reagents. The data evaluation was performed with FlowJo software. We have studied relative contents of the main subsets, i.e., total Т cells (CD3+); Т helpers (CD3+CD4+Th); cytotoxic T cells (CD3+CD8+CTL); natural killers (СD3-CD16+CD56+NK); В cells (CD3-CD19+), and minor lymphocyte subpopulations: double-positive (DP) (CD3+CD4+CD8+); double-negative (DN) (CD3+CD4-CD8-) T cells; NKT (СD3+CD16+CD56+); CD3+CD8bright, CD3+CD8dim, CD3-CD8+NK. Statistical evaluation was carried out with standard GraphPad Prism 5 software. Among the main lymphocyte populations in CSF, T cell were predominant (96.2%), as well as their subpopulations, i.e., CD4Th (53.4%), and CD8+CTL (28.2%), with low amounts of NK (2.2%) and B cells (0.7%). The mean relative content of minor subpopulations (DN or DP T cells, and NKT cells) was, respectively, 5.3, 4.0, and 9%. Age dependence was revealed for the contents of major and minor lymphocyte subsets. With advancing age of the children, the relative numbers of CD3+ and CD4+Тh cells in CSF increase, as well as CD4/CD8 ratio, associated with decreased share of NK cells, like as DN and CD3+CD8dimТ cells. The results obtained are reflect some features of lymphocyte pool in CSF of the children without inflammatory process in CNS. Thus, they may be referred as control values (inflammation-free brain disorders) when studying immune pathogenesis of neuroinfections and other inflammatory diseases of CNS in the children from different age groups.